Konsesi Konservasi Melalui Kebijakan Restorasi Ekosistem di Hutan Produksi - Qodriyatun, Sri Nurhayati (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2016)
Ecosystem restoration in production forest is one of the government’s efforts to improve the damaged production forests by involving private sector through implementation of the conservation concession. Conservation concession is a new concept in forest management which is expected to save the forest, and still provide economic and social benefits for the community. In conservation concession, the ecological, economical, and social aspects were being maintained as one. However, ecosystem restoration is not yet to be implemented with the overall principle of conservation concession, such as the licensing process is not conducted through market mechanism, the application fee is not equally applied between ecosystem restoration concession and other concessions; not transparent, the area is not clean and clear; and no set rule on the possibility of logging in ecosystem restoration concessions. Therefore, the government needs to ensure several things including to reserved the area to be free of conflicts of tenure, to reduce the amount of fee charged, to abolish the rules that granting logging on ecosystem restoration concession, and to provide incentive for the concessions that had managed to restore the production forest. Kebijakan restorasi ekosistem di hutan produksi adalah salah satu upaya pemerintah untuk memperbaiki hutan produksi yang rusak dengan melibatkan swasta melalui penerapan konsep konsesi konservasi. Konsesi konservasi adalah satu konsep baru dalam pengelolaan hutan yang diharapkan dapat untuk menyelamatkan hutan di satu sisi, tetapi tetap memberikan manfaat ekonomi dan sosial bagi masyarakat. Melalui konsesi konservasi, aspek ekologi, ekonomi, dan sosial berjalan bersama dalam satu pengelolaan hutan. Namun pelaksanaan restorasi ekosistem belum menerapkan keseluruhan prinsip konsesi konservasi dan masih terdapat beberapa kelemahan, seperti proses perizinan yang tidak dilakukan melalui mekanisme pasar, penerapan iuran yang diberlakukan sama antara konsesi restorasi ekosistem dengan konsesi lainnya, tidak transparan, areal yang dicadangkan tidak clean and clear, serta adanya aturan dimungkinkannya penebangan di konsesi restorasi ekosistem. Untuk itu, ke depan pemerintah perlu menjamin lahan yang dicadangkan bebas dari konflik tenurial, pengurangan besaran iuran yang dibebankan, dihapuskannya aturan pemberian izin penebangan pada konsesi restorasi ekosistem, dan memberikan insentif bagi konsesi yang berhasil merestorasi kawasan hutan produksi.